Project-Based Learning for the 21st Century: skills for the future - Magdalena, Tabita Angelina; Utami, I.G.A Lokita Purnamika; Adnyayanti, Ni Luh Putu Era (Jurnal Penelitian Mahasiswa Indonesia, 2024)
One of the factors determining student success is the selection of the right method, the method that best suits the times in the 21st century is project-based learning (PjBL). PjBL is a learning approach that emphasizes learning through collaborative projects. This article discusses the implementation of Project-Based Learning (PBL) as a relevant learning method to develop skills required in the 21st century. PjBL not only helps students acquire knowledge, but also develop critical thinking skills, creativity, and teamwork. With a focus on developing 21st century skills, PBL provides benefits in increasing students' learning motivation and engagement in the learning process. This article also provides insights into the implementation of PjBL in classrooms and also identifies challenges that may be faced in implementing PjBL and offers solutions to overcome these challenges.